2011
DOI: 10.2139/ssrn.1974368
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Efficiency of the BRICSs' National Innovation Systems: A Comparative Study Based on Dea and Panel Data Analysis

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 16 publications
0
24
0
1
Order By: Relevance
“…For example, Austria's and Denmark's low efficiency may be also found in the work of Cai (2011) , who studied the innovation efficiency of 22 countries, including BRICS and G7. Additionally, this study showed that Norway, Belgium, Italy, and France have a relatively moderate efficiency score.…”
Section: Efficiency Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…For example, Austria's and Denmark's low efficiency may be also found in the work of Cai (2011) , who studied the innovation efficiency of 22 countries, including BRICS and G7. Additionally, this study showed that Norway, Belgium, Italy, and France have a relatively moderate efficiency score.…”
Section: Efficiency Resultsmentioning
confidence: 88%
“…Some of these studies applied a second level econometric analysis to examine the effect of environmental factors to efficiency scores ( Afzal (2014), Cai (2011), Guan (2010), Cullmann, Schmidt-Ehmcke, andZloczysti (2011), Guan and Chen (2012), Nasierowski and Arcelus (2003) ). Tobit has been mostly used while more recently Matei and Aldea (2012) and Afzal (2014) employed bootstrap for getting bias corrected estimations.…”
Section: Evaluating Innovation Systems With Deamentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies indicated a significant relationship between innovation outcomes and R&D activities and investment in organizations (Kou et al, 2016;Liu et al, 2015;Wiseman, Anderson 2012;Cai, 2011). According to Morris-King (2014) highly active industrial partners.…”
Section: Generation Of New Knowledge and Innovation Outputsmentioning
confidence: 99%